Was Hugo Chávez to Blame? Media Depictions of Polarisation in Venezuela, 1998–2013. - MACLEOD, ALAN (Bulletin of Latin American Research, 2020)
This article explores how seven leading western newspapers covered the topic of polarisation in Venezuelan society during the Chávez era. It found that the media largely ignored the debate as to whether Hugo Chávez was the catalyst or consequence of polarisation. It virtually unanimously presented him as a divisive, polarising character destroying democracy, contrary to the lived experiences of many Venezuelans, while ignoring other possible explanations for the polarisation. It also found that there was a strong similarity in how the liberal and conservative, British and American press covered the issue, with virtually no differences in explanations or outlook, thus manufacturing consent for the elite view of the issue.